In‐use emissions testing of diesel‐driven buses in Southampton: is selective catalytic reduction as effective as fleet operators think?. Issue 6 (2nd March 2018) - Sowman, Jonathan; Box, Simon; Wong, Alan; Grote, Matt; Laila, Dina S.; Gillam, Gus; Cruden, Andrew J.; Preston, John M.; Fussey, Peter
Abstract : Despite the continuously tightening emissions legislation, urban concentrations of nitrogen oxides (NO x ) remain at harmful levels. Road transport is responsible for a large fraction, wherein diesel engines are the principal culprits. Turbocharged diesel engines have long been preferred in heavy duty applications, due to their torque delivery and low fuel consumption. Fleet operators are under pressure to understand and control the emissions of their vehicles, yet the performance of emissions abatement technology in real‐world driving is largely unquantified. The most popular NO x abatement technology for heavy duty diesel vehicles is selective catalytic reduction. In this work, the authors empirically determine the efficiency of a factory‐fitted selective catalytic reduction (SCR) system in real‐world driving by instrumenting passenger buses with both a portable emissions measurement system and a custom‐built telematics unit to record key parameters from the vehicle diagnostics systems. They find that even in relatively favourable conditions, while there is some improvement due to the use of SCR, the vehicles operate far from the design emissions targets. The archival value of this study is in quantification of real world emissions versus design levels and the factors responsible for the discrepancy, as well as in examination of technologies to reduce this difference.